Evaluasi Usability Aplikasi Mobile Karir.com Menggunakan Metode Heuristic Evaluation - Denis Mafira Ramdhan; Satrio Hadi Wijoyo; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Karir.com is the first career portal in Indonesia and a platform for recruitment of employee through online. Karir.com can be access through website and mobile application. However, in the Karir.com mobile application there is a usability problems when the users use the application. Examples, there is no confirmation when applying a job and there is no cancellation feature after applying a job. In order to have information on other problems which are more complex and specific, heuristic evaluation can be done as it involves usability expert as an evaluator. Heuristic evaluation used can be divided into 10 Nielsen's heuristics principle. The 10 Nielsen's heuristics principle are visibility of system status, match between systems and real world, user control and freedom, consistency and standards, error prevention, rather than recall recognition, flexibility and efficiency of use, aesthetic and minimal design, help users recognize, diagnose, and recover from errors and help and documentation. The evaluators involve in the evaluation process consist of 4 people evaluators. In the first analysis, the evaluators discovered 25 usability problems. From the total of 25 usability problems, it includes all 10 aspects from Nielsen's usabiliity problems. The highest frequency of the problem is at the consistency and standards (H-4) with the percentage of 22.5%. furthermore, the highest average of severity rating is at the help and documentation (H-10) of heuristic principle with the value of 3. After the implementation of recommendation improvement results, there is no problem found on the usability in the early evaluation, and only 1 new usability problem found in further evaluation with the severity rating value of 1. The improvements made are very effective with the decreasing of total problems found.